Ameliorative efficacy of novel multi herbal formulation (AKSS16-LIV01) upon Haematological modulations induced by fixed dose combination of tramadol hydrochloride/paracetamol (THP) - Darbar, Soumendra; Saha, Srimoyee; Pramanik, Kausikisankar; Chattopadhyay, Atiskumar (Journal of Drug Delivery and Therapeutics, 2020)
Background: Tramadol hydrochloride/paracetamol (THP) a fixed dose combination (FDC) is widely spread analgesic used to treat moderate to moderately severe pain. Over dose or chronic use of this fixed dose combination produce serious adverse effects.  An acute Tramadol hydrochloride/paracetamol (THP) overdose can lead to a fatal liver damage.Objectives: There is a worldwide need to develop a safe and symptomatic medication which controls the different medical complications. Materials and Methods: Healthy adult swiss albino mice were assigned to four groups of six mice each according to their weights. Group-I serve as control, Group-II received Multi herbal formulation (AKSS16 LIV01) 400 mg/kg/day, Group-III received Tramadol hydrochloride/paracetamol (THP) 1.68 g / 300ml water and Group-IV received THP along with AKSS16-LIV01 (400 mg/kg). Blood samples were collected from the retro orbital plexus of each animal to determine various blood parameters and liver transaminase. Results: Administration of THP showed decline body weight, food consumption and water intake in mice whereas treatment with Multi herbal formulation (AKSS16-LIV01) normalized the same as compared with untreated animals. Treatment with THP (Group-III) decline the packed cell volume (PCV), haempglobin (Hb), means cell volume (MCV), means cell hemoglobin (MCH) and greater the white blood cell (WBC) compared with control. Pre-treatment with AKSS16-LIV01 significantly (p